Perceptions and expectations of parents regarding their position in a French NICU: quantitative and qualitative approaches - Véronique Thébaud; Jacques Sizun; Magdalini Dargentas (BMJ Open)
Objectives To assess perceptions, expectations, and concerns of parents of preterm infants regarding their position during hospital admission in the neonatal intensive care unit.Design Data were analysed from two studies, using complementary methods (quantitative and qualitative). Study I surveyed parents via a questionnaire, and study II was a reanalysis of interviews with fathers, collected in a previous study.Setting Neonatology department in a French tertiary care university hospital that promotes the Newborn Individualised Care and Assessment Program (NIDCAP).Participants In both studies, participants had a premature child admitted for any level of care in the neonatal intensive care unit.Results For study I, about half (33) of eligible families participated in the questionnaire survey, and for study II, we reanalysed interviews with 20 fathers. In both analyses, parents were satisfied overall with their involvement in the care of their child. In both studies, however, they expressed that they had expected to be better informed about their child’s condition and more involved in medical decision-making. Parents also reported relational issues with some healthcare practitioners who made them feel judged, unheard or not competent to discuss their child’s case. These concerns were not reported for NIDCAP staff. Respondents in both studies also described insufficient contact with physicians and an inability to obtain rest in the room with their child.Conclusion Provision of training to healthcare practitioners regarding information that parents request and doing so respectfully might be keys to fulfilling parent-reported needs. Such improvements could facilitate parental empowerment and involvement.